Effects of Movement Control Biofeedback Exercise Training on Joint Position Sense and Dysfunction in Patients with Chronic Neck Pain - Dong- Il Seol; Hyung -Min Yoon (Asian Society of Kinesiology, 2019)
OBJECTIVES The purpose of this study was to investigate the effect of visual neck movement control biofeedback during neck movement control exercise training for eight weeks on joint position sense and dysfunction in neck. METHODS The subjects were 21 women who had chronic neck pain during the last six months. They were divided into Experimental Group (EG, n=10; 47.5±5.4 yrs.) and Control Group (CG, n=11; 45.0±3.7 yrs.). Both groups carried out neck movement control exercise training over a period of 8 weeks. The visual biofeedback informed by the neck's moving which was displayed in real time on three axes (X: flexion & extension, Y: rotation, Z: lateral flexion) on a smart phone devise screen wirelessly linked to initial measurement units were provided only to EG subjects during the neck movement control exercise. The dependent variables were joint position sense and neck disability index, which were tested in a pre-test before and in a post-test 4 and 8 weeks after the two types of exercise training programs. The repeated measurement two-way ANOVA was performed to test mean difference between groups and measurements, and the effect of interactions between them on the significant level of α=.05. RESULTS First, there were significant differences between groups in joint position sense of neck and cervical flexion. Second, there were significant differences between measurements of 1) cervical rotation, cervical lateral flexion, cervical flexion, cervical extension in the joint position sense test, 2) neck disability indexes. Third, the effect of interaction was significant in cervical lateral flexion and cervical flexion of joint position sense test, and neck disability indexes. CONCLUSIONS It was concluded that the visual neck movement control biofeedback provided during the 8 weeks movement exercise training using initial measurement unit improved joint position senses in cervical lateral flexion and cervical flexion, and resolved various neck dysfunction in chronic neck pain patients.